A Comparison of Functional and Radiographic Outcomes following Microfracture with Extracellular Matrix Augmentation versus Osteochondral Autograft Transplantation for the Treatment of Medium-Sized Osteochondral Lesions of the Talus. Issue 7 (31st July 2020) - Sofka, Carolyn; Cabe, Taylor; Deland, Jonathan; Drakos, Mark; Patel, Karan
Objectives: The aim of this study is to directly compare clinical outcomes following the treatment of medium-sized osteochondral lesions of the talus (OLTs) using a microfracture technique augmented with Extracellular Matrix and Bone Marrow Aspirate Concentrate (MFX) versus OAT to determine which treatment is superior for medium-sized lesions. Methods: Patients treated for an OLT between 2015 and 2018 by a single surgeon, fellowship-trained in sports medicine and foot and ankle, were screened for this study. Retrospective chart review determined treatment, lesion size, lesion location, concurrent injuries, and demographic information. Patients at a minimum of 12 months follow-up, treated with MFX or OAT, and lesions sized 80-165mm2 were eligible for inclusion. All surgical repairs were augmented with an adjuvant mixture of micronized cartilage extracellular matrix and bone marrow aspirate concentrate (ECM-BMAC). Patient-reported functional outcomes were collected through our institution's prospective Registry database. Patients treated prior to March 2016 were administered preoperative Foot and Ankle Outcome Score questionnaires. Those treated after this date were administered preoperative Physical Function, Pain Interference, Global Physical Health, Global Mental Health, Depression, and Pain Intensity Patient-Reported Outcome Information System (PROMIS) domains. Both FAOS and PROMIS were administered postoperatively. Postoperative MRIs were assessed using a modified magnetic resonance observation of cartilage repair tissue (MOCART) score. Student's paired and two-group t-tests were used to evaluate for statistically significant pre-to-postoperative change and differences between procedure groups (p less than 0.05). Results: Twenty-seven patients treated with MFX (age range, 14-58) and twenty-three patients treated using OAT (age range, 22-64) were identified. All OAT patients received a single-plug transplantation. The final average lesion size ± standard deviation (SD) for patients treated with MFX was 115.44mm2± 22.51 (range, 156-80mm2) and 121.78mm2± 23.98 (range, 165-80mm2) for those treated using OAT (p=0.34). On average, functional outcome scores improved pre-to-postoperatively across all scales within both groups. Statistically significant improvements were detected in PROMIS Physical Function (Δ=8.32, p=0.01), Pain Interference (Δ=-7.15, p=0.02), Global Physical Health (Δ=5.87, p=0.03), and Pain Intensity (Δ=-7.06, p=0.05) domains for the MFX cohort. For the OAT patient group, significant pre-to-postoperative change was seen in the FAOS subcategories of Pain (Δ=28.70, p=0.03), Sports Activities (Δ=43.12, p<0.01), and Quality of Life (Δ=43.75, p=0.01); overall FAOS score (Δ=29.93, p=0.01); and PROMIS Physical Function (Δ=13.66, p=0.01), Pain Interference (Δ=-14.58, p<0.01), Global Physical Health (Δ=12.2, p=0.01), Depression (Δ=-4.13, p=0.02), and Pain Intensity (Δ=-16.56, p=0.02) domains. On average, with the exception of the postoperative Sports Activities subscale, postoperative FAOS and pre-to-postoperative change in FAOS were higher and greater in the OAT patient group. Similarly, on average, the OAT group had better PROMIS t-scores indicating higher function or less pain and greater pre-to-postoperative change in each PROMIS domain. The OAT cohort's average postoperative Pain Interference t-score (± SD) of 43.09 (± 5.81) and Depression t-score of 40.06 (± 6.84) were significantly lower than their respective counterparts in the MFX cohort: 50.08 (± 9.47) for Pain Interference and 48.09 (± 7.86) in Depression. (Table 1) Finally, the mean overall MOCART score was 55.67 (± 24.11) within the MFX cohort, average follow-up 15.29 months, and 71 (± 15.60) within the OAT cohort average follow-up 15.8 months. This difference was also statistically significant (p=0.04). Conclusion: The OAT group had a higher MOCART score indicating the use of a single osteochondral autograft plug may result in better structural repair than microfracture abrasion chondroplasty augmented with a mixture of adjuvant ECM-BMAC. In addition, higher average FAOS scores, better average PROMIS t-scores, and greater pre-to-postoperative change in the OAT patient group indicate functional results may be better in this group as well. Specifically, significantly lower Pain Interference and Depression domains and significantly higher Global Mental Health scores indicate patients treated using OAT experience less pain and better psychological benefits postoperatively compared to patients treated using MFX. These results suggest filling the lesion with transplanted autograft bone and native, hyaline cartilage may perform better than and the biomechanically inferior fibrocartilage produced following microfracture even when augmented with adjuvant therapy. OAT may result in better overall clinical outcomes, specifically in a population of patients with medium sized lesions (range, 80 mm2 -165 mm2).